Monitoring RNA Release from Human Rhinovirus by Dynamic Force Microscopy - Kienberger, Ferry (American Society for Microbiology, 2004)
Human rhinoviruses were imaged under physiological conditions by dynamic force microscopy. Topographical images revealed various polygonal areas on the surfaces of the 30-nm viral particles. RNA release was initiated by exposure to a low-pH buffer. The lengths of the RNAs that were released but still connected to the virus capsid varied between 40 and 330 nm, whereas RNA molecules that were completely released from the virus were observed with lengths up to 1 μm. Fork-like structure elements with 30-nm extensions were sometimes resolved at one end of the RNA molecules. They possibly correspond to the characteristic multi-stem-loop conformation, the internal ribosomal entry site, located at the 5′ region of the genome. This study demonstrates that dynamic force microscopy can be used to study viral RNA release in situ under physiological conditions.